2016
DOI: 10.1371/journal.ppat.1005427
|View full text |Cite
|
Sign up to set email alerts
|

Selective Degradation of Host RNA Polymerase II Transcripts by Influenza A Virus PA-X Host Shutoff Protein

Abstract: Influenza A viruses (IAVs) inhibit host gene expression by a process known as host shutoff. Host shutoff limits host innate immune responses and may also redirect the translation apparatus to the production of viral proteins. Multiple IAV proteins regulate host shutoff, including PA-X, a ribonuclease that remains incompletely characterized. We report that PA-X selectively targets host RNA polymerase II (Pol II) transcribed mRNAs, while sparing products of Pol I and Pol III. Interestingly, we show that PA-X can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
252
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(276 citation statements)
references
References 66 publications
24
252
0
Order By: Relevance
“…3A). Several studies have reported that the PA-X protein is involved in the inhibition of host protein expression (15,16,18,20,35,42,43). In order to generate a PA-X-deficient construct, the frameshift sequence was changed to two different sequences to potentially inhibit PA-X expression (UCC UUC AGA or AGC UUC AGA) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3A). Several studies have reported that the PA-X protein is involved in the inhibition of host protein expression (15,16,18,20,35,42,43). In order to generate a PA-X-deficient construct, the frameshift sequence was changed to two different sequences to potentially inhibit PA-X expression (UCC UUC AGA or AGC UUC AGA) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to generate a PA-X-deficient construct, the frameshift sequence was changed to two different sequences to potentially inhibit PA-X expression (UCC UUC AGA or AGC UUC AGA) (Fig. 3A) (15,16,18,20,35,42,43). Importantly, none of the approaches used for the abolition of the ribosomal frameshift motif changed the PA amino acid sequence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations